A case report of systemic embolic events associated with atrial fibrillation. Issue 1 (25th August 2016) - Nakano, Hidehiko; Yamagami, Hiroshi; Ofuchi, Hisashi
Abstract : Case: An 82‐year‐old woman who had atrial fibrillation was found unconscious and was brought to the emergency department by ambulance. Her Glasgow Coma Scale score was 3, and an electrocardiogram showed ST segment elevation in V3 and V4. Cardiac ultrasonography showed left ventricular asynergy in the anterior wall, septum, and apex. Although dissection of the aorta was suspected, contrast computed tomography showed multiple arterial thromboses, including bilateral common carotid arteries and poor contrast in the left ventricle. Diffusion‐weighted images of magnetic resonance imaging showed a diffuse high‐intensity area in both cerebral cortices. Outcome: The diagnosis was multiple arterial thromboembolisms associated with atrial fibrillation. There was no available treatment because of massive multiple lesions and the patient died within 24 h of presentation. Conclusion: Extracranial systemic embolic events other than cerebral embolism could be critical complications associated with atrial fibrillation.